(3GdEfgGA HGdEOGQI GdefaQOI dYbO GdYed ZjQ eMOO GdeOI ai bGfhf GdYed GdeUQj (B: s (3OQGSI ebGQfI (B/ s - (3CMeO YHOGddg eMeO Ydis; (3CMeO MSf GdHQYi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3JfGhdJ gPg GdQSGdI OQGSI ehVhY (B" (3GdEfgGA HGdEOGQI GdefaQOI dYbO GdYed ZjQ eMOO GdeOI ai bGfhf GdYed GdeUQj(B"((3OQGSI ebGQfI(B): (3h Pdc fXQG deG dgPG GdehVhY ef CgejI YdejI h YedjI(B. (3h bO JfGhdJ gPg GdOQGSI GdebGQfI HbhGfjf KdGK Ohd YQHjI(B: (3h gj GdSYhOjI h GdEeGQGJ h GdchjJ(B: (3h Pdc dCf gPg GdOhd JYO ef CcKQ GdOhd GdYQHjI GSJbHGdG ddYeGdI GdCLfHjI h NGUI GdYeGdI GdeUQjI(B. (3hJfGhd GdOQGSI QDjI ehLRI dCge CMcGe EfgGA YdGbI GdYed ai eYGjjQ GdYed GdOhdjI h GdYQHjI hPdc ddhbha Ydi eOi GMJQGe GdbhGfjf eMd GdOQGSI dJdc GdCMcGes
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdJTQjYGJ GdELJeGYjI, (B2010s
(3HHdjhLQGajG(B: (3UaMGJ (B351-364s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdJTQjYGJ GdELJeGYjIs; (3GdEfgGA HGdGQGOI GdefaQOIs; (3GdaUd h GdaSNs; (3GfgGA YdGbI GdYed ai eYGjjQ GdYeds; (3GdbGfhf GdebGQfs; (3GdGfgGA GdeTQhYs; (3GdGfgGA ZjQ GdeTQhYs; (3GKGQ GdGfgGAs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdJTQjYGJ GdELJeGYjIs